A novel low‐grade nasopharyngeal adenocarcinoma characterized by a GOLGB1‐BRAF fusion gene. Issue 1 (29th September 2020) - Bubola, Justin; Antonescu, Cristina R.; Weinreb, Ilan; Swanson, David; De Almeida, John R.; MacMillan, Christina M.; Dickson, Brendan C.
Abstract: Nasopharyngeal adenocarcinoma is a rare malignancy that is classified into conventional/surface‐ and salivary‐types. Herein we report the case of a 52‐year‐old male who presented with a right nasopharyngeal mass and right‐sided hearing loss. Diagnostic imaging revealed a circumscribed 1.7 cm mass centred in the right antero‐lateral aspect of the nasopharynx. A biopsy showed a gland‐forming neoplasm that was in continuity with the surface epithelium. The tumor exhibited a nested to micro‐papillary architecture, with mild cytologic atypia. Immunohistochemistry demonstrated diffuse staining for CK7, SOX10, and p16; the abluminal layer was highlighted by CK5 and p63, while the luminal cells expressed CD117. The tumor was not amenable to subclassification and was diagnosed as a low‐grade nasopharyngeal adenocarcinoma, not otherwise specified (NOS). Subsequent RNA sequencing was performed which identified a novel GOLGB1‐BRAF fusion product. Based on its unique morphology and molecular findings, this is presumed to represent a novel subtype of nasopharyngeal adenocarcinoma. In addition to being of diagnostic relevance, this fusion may ultimately represent a potential therapeutic target.